The change rule of smoke dispersion and temperature evolution in fires within lithium iron phosphate energy storage prefabricated cabin - ZHANG Yin; QIN Chaoqun; TIAN Shuangshuang; GE Zhichao; DONG Jun; ZHANG Xiaoxing (电力工程技术)
With the large-scale application of electrochemical energy storage, the safety of energy storage prefabricated cabin has become increasingly prominent. The study of the differences in energy storage prefabricated cabin fires under different thermal runaway positions in the energy storage prefabricated cabin can help to design more effective monitoring and fire extinguishing systems, and to improve the safety performance of the energy storage prefabricated cabin. Therefore, it is of great significance to simulate and study the change rule of smoke dispersion and temperature evolution in energy storage prefabricated cabin under different thermal runaway positions. Based on direct numerical simulation and vortex simulation, a numerical model of lithium iron phosphate energy storage prefabricated cabin based on the size of the actual energy storage prefabricated cabin is studied, and the t2 model which is more in line with the development of the fire situation compared with the stable fire model, and investigated the change rule of the smoke dispersion and temperature inside the prefabricated cabin by simulating the fire situation with different thermal runaway positions. The simulation results demonstrate that smoke displays distinct dynamic behaviors depending on the thermal runaway positions within the energy storage prefabricated cabin. When thermal runaway positions occur closer to the bottom, smoke exhibits swifter movement and the cabin fills up in a shorter time. Additionally, as the thermal runaway positions above 1.85 meters approach the top, accompanied by significant temperature fluctuations. Notably, there is a noticeable amplification in the temperature disparity along the horizontal axis of the energy storage prefabricated cabin. Moreover, the design scheme of the fire extinguishing system for a standard energy storage prefabricated cabin with a rated capacity of 1.2 MW ·h is analyzed. This perfluorohexane fire extinguishing system, with a sprinkler intensity of 20 L/(min ·m2), a sprinkler angle of 120°and a particle size of 50 μm, can successfully controls fires and mitigates fire damage. The research results in the article can provide theoretical guidance for the distributed deployment strategy in energy storage prefabricated cabin and fire safety design of monitoring and warning devices.